Konfigurasi dan Penempatan Alat Ukur Beban untuk Penentuan Nilai Track Access Charge Berbasis Data Realisasi Perjalanan Kereta Api - Yul Y. Nazaruddin; Arbie Sianipar; Nadana A Aziz; Jonathan Chandra; Rahmat Maulana; Tua A. Tamba; Sigit P. Santosa (Jurnal Penelitian Transportasi Darat, 2021)
ABSTRACTConfiguration and Placement of Load Measuring Instruments for Determination of Track Access Charge Values Based on Train Travel Realization Data: Based on the regulation of the Directorate General of Railways of the Ministry of Transportation year 2015, the cost element that is considered as non-tax revenue comes from the utilization of government’s railway infrastructures and is known as the Track Access Charge (TAC). The currently used method for the determination of the TAC value often causes debates as it is considered not based on the actual utilization of the railway infrastructure but rather dependent on maintenance costs of the railway infrastructure that are spent by the government. This paper reports the results of a research study which was conducted to evaluate methods that can be used to evaluate the TAC value based on measurement data of railway operational realization in the field. Based on the historical data of train operation, this research design a configuration of weigh-in-motion (WIM) system which can calculates the gross tonnage and travel distance of all trains over a predetermined time period. This research also determines 20 train stations that spread across eight operational regions across the Java island as the primary locations for WIM system placements to help determines the TAC value that is more realistic and effective.Keywords: railway management; track access charge; weigh-in-motion; sensor placement.ABSTRAKBerdasarkan Peraturan Direktur Jenderal Perkeretaapian di Kementerian Perhubungan tahun 2015, komponen biaya yang diperhitungkan untuk penerimaan negara bukan pajak (PNBP)berasal dari penggunaan prasarana perkeretaapian milik negara atau sering disebut Track Access Charge (TAC). Penentuan nilai TAC yang digunakan saat ini masih sering menimbulkan perdebatan karena dianggap tidak didasarkan pada tingkat penggunaan prasarana, melainkan pada biaya pengelolaan/pemeliharaan seluruh prasarana perkeretaapian yang dialokasikan pemerintah. Penelitian ini bertujuan untuk melakukan evaluasi terkait penentuan nilai TAC berbasis data pengukuran realisasi aktual pengoperasian kereta api (KA) di lapangan. Berdasarkan data historis operasional KA yang tersedia serta informasi yang dibutuhkan dalam penentuan TAC, penelitian ini merancang konfigurasi sistem weigh-in-motion (WIM) yang dapat menghitung tonase dan jarak tempuh operasional seluruh KA dalam rentang waktu tertentu yang diinginkan. Penelitian ini juga menentukan 20 stasiun KA yang tersebar di delapan daerah operasional KA di Pulau Jawa sebagai lokasi penempatan sistem WIM untuk penentuan nilai TAC yang lebih realistis dan efektif.Kata Kunci: manajemen perkeretaapian, track access charge; weigh-in-motion; penempatan sensor.